The use of action learning as a group problem solving process in Sibu Municipal Council - Hii, Chang Kee (1998)
Group problem solving takes various forms in Sibu Municipal Council. The common ones are committees, task forces, quality control circles and work teams. Despite very strong top management commitment to promote group problem solving, the employees have not been very receptive of the practice. This became a thematic concern of the organisation. The study attempted to explore the use of action learning as group problem solving process in Sibu Municipal Council using an action research approach. An action research group was formed with researches as the facilitator. Each research member established his or her own action learning set to embark on group problem solving projects on real organizational issues.